Public Swearing In Ceremony for Judges Charles Hamlin, Gene Gomes, Ralph Nunez, Mario Olmos and Victor Papadakis at Veterans' Memorial Auditorium - Watkins, Howard::::::::: (1983)
Robert Klein and Judge Victor Papadakis; Deran Koligian on right